A review on optimistic development of polymeric nanocomposite membrane on environmental remediation. (February 2023) - Cheng, Yueqin; Xia, Changlei; Garalleh, Hakim AL.; Garaleh, Mazen; Lan Chi, Nguyen Thuy; Brindhadevi, Kathirvel
Abstract: Current health and environmental concerns about the abundance and drawbacks of municipal wastewater as well as industrial effluent have prompted the development of novel and innovative treatment processes. A global shortage of clean water poses significant challenges to the survival of all life forms. For the removal of both biodegradable and non-biodegradable harmful wastes/pollutants from water, sophisticated wastewater treatment technologies are required. Polymer membrane technology is critical to overcoming this major challenge. Polymer matrix-based nanocomposite membranes are among the most popular in polymer membrane technology in terms of convenience. These membranes and their major components are environmentally friendly, energy efficient, cost effective, operationally versatile, and feasible. This review provides an overview of the drawbacks as well as promising developments in polymer membrane and nanocomposite membranes for environmental remediation, with a focus on wastewater treatment. Additionally, the advantages of nanocomposite membranes such as stability, antimicrobial properties, and adsorption processes have been discussed. The goal of this review was to summarize the remediation of harmful pollutants from water and wastewater/effluent using polymer matrix-based nanocomposite membrane technology, and to highlight its shortcomings and future prospects. Graphical abstract: Image 1 Highlights: This review emphasize the importance of filtration water and industry effluent. Disadvantages of synthetic polymer in water and effluent treatment is discussed. Optimistic development of polymeric nanocomposite membrane for water filtration. Selective nanoparticles impregnated nanocomposites membrane application. Practically possible future perspectives have been suggested in this review.